Social Policy of Science Viewed from the Aspect of Sociology - Research and some Discussions - Huan, Tran Van; Hoang, Nguyen Huu (VNU Journal of Science: Policy and Management Studies, 2020)
Sociology and social policy of science are one of the new sciences but full of potential for development in Vietnam. This paper combines more methodologies to analyze the basic relationships of them by some aspects of practice. The consequences bring more new things, to be looked down on or even denied about relating between two of these sciences.